DAKWAH KAMPUS : TRANSFORMASI DAKWAH TEKSTUAL KE DAKWAH KONTEKTUAL RASIONAL - Muhammad Ridwan; Andi Edwin Rewira (Universitas Islam Depok, 2021)
Campus da'wah is dynamic and can be carried out with methods that are appropriate to the situation and conditions. Da'wah is one of the efforts to bridge the wide gap and act as a trigger for social change. Campus, Campus is an intellectual entity that has an important role in implementing Islamic values ​​for the campus community. Campus da'wah is a form of activity to transform Islamic values ​​in a rational contextual perspective. In an effort to carry out its activities, da'wah remains important and maintains the basic values ​​of Islamic teachings. In conducting this campus da'wah research, the author uses a qualitative descriptive research method with a literature study accompanied by references to facts in the field. This research is motivated by the condition of the people who currently understand that their religion is still textual and not many have a contextual perspective. For example, during the Covid-19 pandemic where attitudes, places and distances occur, campus da'wah can still be carried out by following the health protocols set by the government, namely using masks and maintaining distance.